College English teaching in China: opportunities, challenges and directions in the context of educational internationalization. (2nd September 2017) - Li, Cuiying; Fang, Zhihui
ABSTRACT: This essay, based on an interview with an internationally renowned scholar of language and literacy education, addresses a range of issues that is of current interest and significance to English teachers in China's higher education context.